ZFP36-family RNA-binding proteins in regulatory T cells reinforce immune homeostasis - Beatriz Sáenz-Narciso; Sarah E. Bell; Louise S. Matheson; Ram K. C. Venigalla; Martin Turner (Nature Communications)
Abstract RNA binding proteins (RBP) of the ZFP36 family limit the differentiation and effector functions of CD4 and CD8 T cells, but little is known of their expression or function in regulatory T (Treg) cells. By using Treg cell-restricted deletion of Zfp36 family members we identify the role of Zfp36l1 and Zfp36l2 in Treg cells to maintain immune homeostasis. Mice with Treg cells deficient in these RBP display an inflammatory phenotype with an expansion in the numbers of type-2 conventional dendritic cells, T effector cells, T follicular helper and germinal center B cells and elevated serum cytokines and immunoglobulins. In the absence of Zfp36l1 and Zfp36l2, the pool of cycling CTLA-4 in naïve Treg cells is reduced, Treg cells are less sensitive to IL-2 and IL-7 but are more sensitive to IFNγ. In mice lacking both RBP in Treg cells, the deletion of a single allele of Ifng is sufficient to ameliorate the pathology. Our results indicate that ZFP36L1 and ZFP36L2 regulate the availability of IFNγ and are required for the maintenance of Treg cell stability. Thus, ZFP36L1 and ZFP36L2 regulate multiple pathways that enable Treg cells to enforce immune homeostasis.